Inovasi Produk Dan Layanan Pada Umkm Oppa Box: Respons Terhadap Perubahan Pasar Dan Kebutuhan Konsumen - Dian Krisna; Novia Yuza Azzahra; Dila Afzurni Hutri; Rahmadhani Putri; Ramdani Bayu Putra (CV. ITTC INDONESIA, 2024)
The purpose of this study is to reveal in detail the innovation strategies carried out by Oppa Box UMKM in responding to changes in consumer preferences and increasing competition in the modern beverage industry. Through an in-depth case study approach, this study provides an in-depth analysis of the types of innovations implemented, the factors that drive and inhibit innovation, and the impact of innovation on organizational performance. In addition, this study also assesses the quality of oppa box information disseminated in online media using comprehensive content analysis techniques. The results of this study are expected to provide a significant empirical contribution to the development of the culinary UMKM innovation framework, especially in the context of the digital era which is characterized by rapid market dynamics and tight competition.